The same but different: clinician-patient communication with gay and lesbian patients - Bonvicini, Kathleen A; Perlin, Michael J (Patient Education and Counseling, 2003)
Surveys estimate that 3-6% of the patients seen by physicians are gay or lesbian. There are unique health risks of gays and lesbians that are important to the clinician in determining an accurate diagnosis, providing patient education, and arriving at an appropriate treatment plan. One of the most significant medical risks of these populations includes avoidance of routine health care and dissatisfaction with healthcare. Many of these healthcare risks are not addressed because of lack of communication based on a number of common assumptions including the assumption that the patient is heterosexual. This article includes a summary of the medical literature through computerized searches to March 2002 in MEDLINE, PsychInfo, HEALTHSTAR, and bibliographies in articles on health care with gay and lesbian patients. The search strategy included health care of gays and lesbians and clinician-patient communication, partner and family issues. Secondly, it will examine common communication barriers and provide strategies for enhancing communication with patients in a gender-neutral, non-judgmental manner including suggestions for enlisting the inclusion of patients' families. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
105 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/042-825-878-960-06X tex.type: [object Object]
Keywords: Clinician-patient communication; Family; Gay; Healthcare; Lesbian; MEDLINE; clinical practice; dept.pch; doctor patient relation; family; female; health care; health hazard; heterosexuality; homosexuality; human; interpersonal communication; male; patient education; patient satisfaction; priority journal; review; treatment planning